Establishment of a Transient and Stable Transfection System for Babesia duncani Using a Homologous Recombination Strategy - Wang, Sen; Li, Dongfang; Chen, Fangwei; Jiang, Weijun; Luo, Wanxin; Zhu, Guan; Zhao, Junlong; He, Lan (Frontiers in Cellular and Infection Microbiology, 2022)
Genetic modification provides an invaluable molecular tool to dissect the biology and pathogenesis of pathogens. However, no report is available about the genetic modification of Babesia duncani, a pathogen responsible for human babesiosis that is widespread in North America, suggesting the necessity to develop a genetic manipulation method to improve the strategies for studying and understanding the biology of protozoan pathogens. The establishment of a genetic modification method requires promoters, selectable markers, and reporter genes. Here, the double-copy gene elongation factor-1α (ef-1α) and its promoters were amplified by conventional PCR and confirmed by sequencing. We established a transient transfection system by using the ef-1αB promoter and the reporter gene mCherry and achieved stable transfection through homologous recombination to integrate the selection marker hDHFR-eGFP into the parasite genome. The potential of this genetic modification method was tested by knocking out the thioredoxin peroxidase-1 (TPX-1) gene, and under the drug pressure of 5 nM WR99210, 96.3% of the parasites were observed to express green fluorescence protein (eGFP) by flow cytometry at day 7 post-transfection. Additionally, the clone line of the TPX-1 knockout parasite was successfully obtained by the limiting dilution method. This study provided a transfection method for B. duncani, which may facilitate gene function research and vaccine development of B. duncani.